What patients think doctors know: Beliefs about provider knowledge as barriers to safe medication use - Serper, Marina (2013)
OBJECTIVE: We examined patient beliefs about provider awareness of medication use, patient-reported prevalence and nature of provider counseling about medications, and the impact of health literacy on these outcomes. METHODS: Structured interviews were conducted at academic general internal medicine clinics and federally qualified health centers with 500 adult patients. Interviewer-administered surveys assessed patients’ beliefs, self-reported prevalence and nature of provider counseling for new prescriptions, and medication review. RESULTS: Most patients believed their physician was aware of all their prescription and over the counter medications, and all medications prescribed by other doctors; while a minority reported disclosing over the counter and supplement use. Among those receiving new prescriptions (n = 190): 51.3% reported physician medication review, 77.4% reported receiving instructions on use from physicians and 43.3% from pharmacists. Side effects were discussed 42.9% of the time by physicians and 25.8% by pharmacists. Significant differences in outcomes were observed by health literacy, age, and clinic type. CONCLUSIONS: There is a sizable gap between what patients believe physicians know about their medication regimen and what they report to the physician. PRACTICE IMPLICATIONS: Discordance between patient beliefs and physician knowledge of medication regimens could negatively impact patient safety and healthcare quality.